A single pre-operative antibiotic dose is as effective as continued antibiotic prophylaxis in implant-based breast reconstruction: A matched cohort study. Issue 5 (May 2015) - Townley, William A.; Baluch, Narges; Bagher, Shaghayegh; Maass, Saskia W.M.C.; O'Neill, Anne; Zhong, Toni; Hofer, Stefan O.P.
Summary Purpose Infections following implant-based breast reconstruction can lead to devastating consequences. There is currently no consensus on the need for post-operative antibiotics in preventing immediate infection. This study compared two different methods of infection prevention in this group of patients. Method A retrospective matched cohort study was performed on consecutive women undergoing implant-based breast reconstruction at University Health Network, Toronto (November 2008–December 2012). All patients received a single pre-operative intravenous antibiotic dose. Group A received minimal interventions and Group B underwent maximal prophylactic measures. Patient (age, smoking, diabetes, co-morbidities), oncologic and procedural variables (timing and laterality) were collected. Univariate and multivariate logistic regression were performed to compare outcomes between the two groups. Results Two hundred and eight patients underwent 647 implant procedures. After matching the two treatment groups by BMI, 94 patients in each treatment group yielding a total of 605 implant procedures were selected for analysis. The two groups were comparable in terms of patient and disease variables. Post-operative wound infection was similar in Group A (n = 11, 12%) compared with Group B (n = 9, 10%; p = 0.8). Univariate analysis revealed only pre-operative radiotherapy to be associated with the development of infection (0.004). Controlling for the effect of radiotherapy, multivariate analysis demonstrated that there was no statistically significant difference between the two methods for infection prevention. Conclusions Our findings suggest that a single pre-operative dose of intravenous antibiotics is equally as effective as continued antibiotic prophylaxis in preventing immediate infection in patients undergoing implant-based breast reconstructions.